Digital Transformation of School Administration through Financial Management Information System (SIMKU) - Niska Ramadani; Yul, Fadlul Amdhi; Abdurrahman, Ariq (Universitas Putra Indonesia YPTK Padang, 2025)
Managing private school administrative data, especially data on Education Development Contribution (SPP) payments, is still a challenge for many institutions that have not implemented information systems optimally. Data collection that is still done manually using spreadsheet applications such as Microsoft Excel has various shortcomings, including limitations in data search, potential input errors, and difficulties in the recapitulation and reporting process. This has an impact on the efficiency of the work of administrative officers and delays in providing information to related parties such as teachers, students, and guardians. Based on this, this study aims to design a web-based SPP payment information system that can help the process of data collection and management of student SPP payments more effectively and efficiently. This system is designed and built using the PHP programming language with the Laravel Framework which is Open Source and supports the development of web applications. MySQL is a database management system that stores all student payment information in a structured manner. The performance results of the designed system have main features such as payment data input, data search based on student name or payment month, automatic recapitulation, and printable payment reports. The system is expected to be able to manage private school financial administration in a more organized, accurate, and fast manner. The final result of the study presents an application of a tuition payment information system that can be utilized by private school administration officers to improve work efficiency and the quality of financial information services to all school residents. In addition, this system can also be further developed for integration with other features such as payment notifications or student achievement system integration.